SYNTHESIS OF WATER SOLUBLE POLYMER BASED ON ACRYLIC ACID AND ACRYLAMIDE BY INVERSE SUSPENSION METHOD - Cong, Trinh Duc; Khoi, Nguyen Van (Vietnam Journal of Science and Technology, 2015)
The copolymerization of acrylic acid (AA) and acrylamide (AM) using ammonium persulfate as initiator was studied by inverse suspension method. Effect of reaction temperature, time and initiator concentration on the average molecular weight was studied in detail. The optimal reaction conditions for the above parameters are 76 oC, 120 min and 1.0 % correspondingly. Morphology of the reaction products was also characterized by scanning electron microscope (SEM).